2000
DOI: 10.1152/ajpendo.2000.279.2.e293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-fat diet, surrounding temperature, and enterostatin on uncoupling protein gene expression

Abstract: Nonshivering thermogenesis induced in brown adipose tissue (BAT) during high-fat feeding is mediated through uncoupling protein 1 (UCP1). UCP2 is a recently identified homologue found in many tissues. To determine the role of UCP1 and UCP2 in thermoregulation and energy balance, we investigated the long-term effect of high-fat feeding on mRNA levels in mice at two different ambient temperatures. We also treated mice with the anorectic peptide enterostatin and compared mRNA levels in BAT, white adipose tissue (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
65
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 39 publications
(44 reference statements)
16
65
0
1
Order By: Relevance
“…Consistent with previous reports, the levels of UCP1 mRNA continued to rise (18,19). The additional increase in UCP1 expression did not prevent weight gain and glucose intolerance, which is in agreement with Margareto et al (31).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous reports, the levels of UCP1 mRNA continued to rise (18,19). The additional increase in UCP1 expression did not prevent weight gain and glucose intolerance, which is in agreement with Margareto et al (31).…”
Section: Discussionsupporting
confidence: 92%
“…In these studies, colipase expression was found to increase in response to a diet with a higher protein content (10,28). Colipase expression has also been shown to be sensitive to surrounding temperature, being maximally expressed at 5°C (19,30). Clearly, the genes encoding lipase and colipase are not coordinately regulated since they respond differently to high-fat diets, dietary protein, and temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vitamins were added to water bottles at a concentration of 1 g/liter and replaced daily (21). The diet containing enterostatin was prepared as described earlier (22).…”
Section: Targeting Construct and Generation Of Mice With Null Allele Formentioning
confidence: 99%